Disaster risk, inequality, and fiscal sustainability - Anh H. Le; Donghyun Park; John Beirne; Mohammed Gazi Salah Uddin (Asian Development Bank (ADB), 2024)
In this paper, we study the implications of climate change on fiscal sustainability and inequality. First, using rich panel data, we show that rising climate-related disaster risks increase government debt and harm fiscal sustainability. We also find that the adverse effect of disaster risks is larger for low-income households, exacerbating inequality. Second, we construct a New Keynesian Dynamic Stochastic General Equilibrium (NK-DSGE) model to examine the implications of the distributional effect of disaster risk. The model features two kinds of households and a fiscal authority. We show that disaster risk has recessionary effects and also causes inequality among households to widen. More specifically, the model indicates that "hand-to-mouth" agents suffer a drop in consumption that is three times larger than that of the Ricardian households. Importantly, we observe a significant rise in sovereign debt due to disaster risk, which poses a challenge to policymakers. Lastly, targeted transfers are recommended but progressive taxes entail a significant fiscal cost.
Keywords: E20; E31; E32; E44; G12; Q54; 330; climate change; disaster risk; physical risk; heterogeneous agent; fiscal policy